State support policies and children's living arrangements. (December 2022) - Potter, Marina Haddock; Littleton, Tenesha; Font, Sarah A.
Abstract: Background: Many children in the United States live apart from their parents, in either formal or informal foster care, due to concerns about child abuse and neglect. Prior research has established a connection between poverty and child maltreatment, but many aspects of state support to families remain unexamined in relation to child living arrangements. Objective: We test welfare access, welfare generosity, work supports, and family supports indicators as predictors of foster care removal rates and nonparental care rates. Participants and setting: We use a population of 51 states, including the District of Columbia, for years 2008 to 2018, totaling 561 state-years. Methods: We utilize negative binomial regression models with state and year fixed effects. Results: We find that one-dollar higher minimum wages are negatively associated with both foster care removal rates (IRR = 0.947, p < 0.001) and nonparental care rates (IRR = 0.975, p < 0.01), but that other state policies are not consistently beneficial. Conclusions: Our results have implications for policies to assist families and reduce child maltreatment.